Perfil demográfico, clínico e laboratorial de pacientes com hiperparatireoidismo secundário: comparação entre tratamento clínico e cirúrgico - Ramos, Luiz Guilherme Fernandes (2020)
Introduction: Mineral and Bone Disease (BMD) is a frequent complication of Chronic Kidney Disease (CKD), called CKD-MBD. Among bone diseases, secondary hyperparathyroidism (SHPT) is common, and parathyroidectomy (PTX) can be indicated in cases of clinical intractability. There are few Brazilian data on the percentage of response to clinical treatment (cinacalcet and vitamin D analogs) and PTX. Methods: We retrospectively evaluated adults in follow-up at the CKD-MBD clinic between 07-07-2017 and 06-30-2018, with at least two consultations in the period. Demographic, clinical, and laboratory information (including total and ionic calcium, phosphorus, alkaline phosphatase, and parathormone - PTH) were collected from electronic charts. Two groups were evaluated: CKD and kidney transplant (Tx). HPTS was defined as PTH> 300 pg/ml in the CKD group and as PTH> 100 pg/ml or ionized Calcium> 5.3 mg/dL in the Tx group. Results: 268 patients with CKD (103 with SHPT) and 134 transplant patients (77 with SHPT) were included. We observed a reduction in the concentration of PTH with either clinical or surgical treatment in both groups. However, analyzing patients with severe SHPT (initial PTH> 800 pg/ml in the CKD group and PTH> 200 pg/ml and/or Total Calcium >11 mg/dl in the Tx group), we observed a better response in patients who were submitted to PTX during follow-up, represented by a more significant drop in PTH in the CKD group and in serum calcium in the Tx group. Conclusion: Clinical treatment with or without cinacalcet is effective in controlling SHPT. However, patients with severe forms should be referred for PTX.